The Curious Case of Multicellularity in the Volvocine Algae - Jiménez-Marín, Berenice; Olson, Bradley J. S. C. (Frontiers in Genetics, 2022)
The evolution of multicellularity is a major evolutionary transition that underlies the radiation of many species in all domains of life, especially in eukaryotes. The volvocine green algae are an unconventional model system that holds great promise in the field given its genetic tractability, late transition to multicellularity, and phenotypic diversity. Multiple efforts at linking multicellularity-related developmental landmarks to key molecular changes, especially at the genome level, have provided key insights into the molecular innovations or lack thereof that underlie multicellularity. Twelve developmental changes have been proposed to explain the evolution of complex differentiated multicellularity in the volvocine algae. Co-option of key genes, such as cell cycle and developmental regulators has been observed, but with few exceptions, known co-option events do not seem to coincide with most developmental features observed in multicellular volvocines. The apparent lack of “master multicellularity genes” combined with no apparent correlation between gene gains for developmental processes suggest the possibility that many multicellular traits might be the product gene-regulatory and functional innovations; in other words, multicellularity can arise from shared genomic repertoires that undergo regulatory and functional overhauls.